THE INFLUENCE OF SALARY AND HEALTH FACILITIES ON EMPLOYEE LOYALTY PT BINA INSAN KAMIL INDONESIA EAST JAKARTA - Ningrum, Dwi Febia; Nurminingsih (Transpublika Publisher, 2023)
In today's competitive business landscape, employee loyalty and well-being are pivotal factors influencing organizational success. PT. Bina Insan Kamil Indonesia, situated in East Jakarta, operates within an environment where retaining skilled and motivated employees is essential. Employee loyalty, often impacted by compensation and workplace amenities, holds the potential to shape the company's performance and overall work culture. The primary goal of this study is to examine the impact of salary on employee loyalty, the relationship between salary and health facilities, and the correlation between health facilities and employee loyalty at PT. East Jakarta Kamil Indonesian Civil Society Development. This study employs a quantitative research approach, viewing reality as measurable and causal, aligned with positivism. Smart Equation Models based on Partial Least Square (PLS) are used for analysis, accommodating various data types and smaller sample sizes. The study covers all PT Bina Insan Kamil Indonesia employees (60 individuals) from February to April 2020, utilizing non-probability total sampling, while data collection involves the Likert scale. The outcomes unveiled significant findings: health facilities wield a substantial impact on employee loyalty at PT. Bina Insan Kamil Indonesia, supported by a T-Statistic test result of 2.323. Similarly, salary demonstrates a notable influence on health facilities, evident from a T-Statistic test result of 225.574. However, the study did not detect a significant effect of salary on employee loyalty, with a T-Statistic test result of 1.823. The study's findings contribute insights into the relationship between salary, health facilities, and employee loyalty in the context of PT. Bina Insan Kamil Indonesia.